The COVID-19 pandemic and the stress it put on college athletics - Williams, M. J.; Mathis, D. M. (The Sport Journal, 2021)
In the early spring of 2020, the COVID-19 Pandemic invaded the United States and brought not only the economy to a stand-still, but college athletics as well. When all spring college sports were halted, along with the NCAA Men`s Basketball Tournament, it created a loss of revenue for college athletics. This forced college presidents and athletic directors to abandon their old business models in order to restructure their athletic budgets, thus moving both college presidents and athletic directors into uncharted waters. Before the COVID-19 Pandemic college athletics had a problem of long-term debt, offering too many sports, employing too many athletic staff, and paying an extraordinary amount in coach`s salary. Because of the Pandemic, college presidents, and athletic directors were forced to make drastic changes that consisted of salary cuts, elimination of sports, and athletic personnel in order to stay afloat. It will take years for athletic budgets to get back to the pre-pandemic era.